LE DON DE L’AMOUR ET DE L’AMITIE DU POEME. LES ENVOIS DE PAUL CELAN A NINA CASSIAN - Giovanni ROTIROTI (Studia Universitatis Babeş-Bolyai. Philologia, 2017)
The poem's gift of love and friendship. The letters sent by Paul Celan to Nina Cassian. The present article is about letters that Paul Celan sent to Nina Cassian and reveals the recovers used by the poet in his communicating to Nina. There are the metaphors taken from Urmuz, this ground-breaking avantguardian not only of the Romanian Literature, and so dear to him, there is all the irony of the surrealists' jokes, the medley of foreign languages used for their secret sonority. And finally, there is the union of “You” and “Me” within the common grief for the loss of their mothers. The magic of the water and its poetical ambivalence will bring Nina towards the life connected with the sea, and Paul towards the death.